Supervision of Education in Improving the Quality of Education in Schools - Inom Nasution; Nadhilah Ajrina; Annisa Hananiyah; Suci Ramadhani; Pitri Ristia Ningsih; Hemalia Putri (Universitas Muhammadiyah Enrekang, 2022)
Education is a necessity for every human being. Through education, each individual can update the knowledge he has in order to keep up with the increasingly sophisticated times, demanding that each individual has the ability to think well. Individuals who have good thinking skills will be able to solve more complex problems than individuals whose thinking ability is still low. The existing reality, until now, is still felt that the condition of education is still not good. Learning facilities are still inadequate, be it the completeness of books in the school library, the use of laboratories that have not been utilized optimally, limited educational facilities and infrastructure, lack of professionalism of educators in teaching, both in preparing teaching materials and in delivering subject matter, lack of discipline of educators, and lack of educator knowledge about the effective learning process so that the real educational goals became unattainable. There are several alternatives that can be done to solve educational problems. First, it provides motivation for the importance of educational supervision for educators. Second, strive for adequate educational facilities and infrastructure. Third, apply the discipline of educators. Educators are an example for every learner.